Conjugate heat transfer in wedged latticework cooling ducts with ejection flow for turbine blades - Binye Yu; Xingwei Li; Jie Li; Shi Bu (Case Studies in Thermal Engineering)
Trailing edge of high temperature turbine blades faces challenge of severe thermal environment due to wedged profile and hence limited cooling spaces. Latticework is a competitive cooling scheme which provides superior structural strength and heat transfer enhancement level, thereby having potential to be used for trailing edge cooling. Besides, conjugate heat transfer characteristics within wedged latticework ducts must be clarified to achieve advanced design. This work fills the gap between geometric complexity and simultaneous consideration of convective-conductive heat transfer. Influence factors including ejection flow configuration, wedge angle and ejection hole dimensions are investigated in sequence in terms of cooling efficiency, temperature distribution, thermo-hydrodynamic performance, relative temperature deviation and thermal-mechanical behavior. The result indicates that heat transfer can be improved by 80 % via optimizing ejection flow configuration. Increasing wedge angle helps enhance heat transfer under the effect of lateral ejection. Expanding ejection hole dimension by varying aspect ratio leads to better thermo-hydrodynamic performance. Besides, structure thermal stress shows a consistent trend with the relative temperature deviation. These findings highlight the role of conjugate heat transfer in trailing edge cooling, also provide guidelines for designing of similar micro-channel heat exchangers where both thermal capability and uniformity are of great importance.